Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1128/aem.51.2.422-424.1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of protozoa from water associated with a legionellosis outbreak and demonstration of intracellular multiplication of Legionella pneumophila

Abstract: At the site of a legionellosis outbreak, amoebae and two ciliates, Tetrahymena sp. and Cyclidium sp., were isolated from cooling-tower water containing Legionella pneumophila. The Tetrahymena sp. and the amoebae repeatedly showed the ability to support intracellular multiplication of L. pneumophila. Both were isolated from cooling towers specifically implicated as the source for the spread of legionellosis. These protozoa may be reservoirs supporting the survival and multiplication of virulent legionellae in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(95 citation statements)
references
References 13 publications
0
90
0
5
Order By: Relevance
“…For instance, coculture experiments in liquid media have shown that amoebae exert an important growth-promoting effect on L. pneumophila. During outbreaks of Legionnaire's disease, the water bodies concerned are usually found to contain significant numbers of free-living amoebae; furthermore, high numbers of Legionella species are found when concentrations of amoebae are high (Barbaree et al, 1986). Moreover, the isolation of L. pneumophila from water is more successful if amoebae are added (Sanden et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, coculture experiments in liquid media have shown that amoebae exert an important growth-promoting effect on L. pneumophila. During outbreaks of Legionnaire's disease, the water bodies concerned are usually found to contain significant numbers of free-living amoebae; furthermore, high numbers of Legionella species are found when concentrations of amoebae are high (Barbaree et al, 1986). Moreover, the isolation of L. pneumophila from water is more successful if amoebae are added (Sanden et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Grazing by heterotrophic protists is a major source of bacterial mortality in soil (Clarholm, 1981;Ekelund et al, 2002), marine (Barbaree et al, 1986;Epstein & Shiaris, 1992) and freshwater (Sanders et al, 1989;Iriberri et al, 1995) systems and is considered to be a major trophic pathway whereby the biomass produced by bacteria, cyanobacteria and algae re-enters the food web (Azam et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, not all bacteria are ingested and digested by protozoa, some escape protozoan ingestion for a number of reasons, including their cell size (Šimek & Chrzanowski, 1992;Jürgens & DeMott, 1995;Kinner et al, 1998;Posch et al, 1999). Some are ingested but have evolved strategies of evading digestion and even multiplying within protozoa, the prototypical example being Legionella pneumphila (Rowbotham, 1980;Barbaree et al, 1986;Brown & Barker, 1994;Molmeret et al, 2005). It is also frequently reported that L. pneumophila uses similar mechanisms to invade protozoan and mammalian cell lines (Segal & Shuman, 1999;Molmeret et al, 2005); thus protozoa have been termed as 'trojan horses' (Brown & Barker, 1994) or 'biological gymnasia' whereby intraprotozoan cells train for their encounter with the more evolved mammalian cells (Harb et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Tetrahymena spp. are ciliated protozoa that, depending on the incubation temperature, can support the growth of Legionella (Fields et al, 1984;Barbaree et al, 1986;Berk et al, 2008). In the species Tetrahymena tropicalis, L. pneumophila is efficiently ingested but does not replicate inside food vacuoles, in spite of resisting digestion.…”
Section: Introductionmentioning
confidence: 99%